Development and characterization of anonymous nuclear markers to determine genetic variation in two groupers species and their hybrids - Ahmad Zaidi Tani (2015)
Grouper (Genus: Epinephe/us) represent one of the high value fisheries resource in Malaysia and several inter-specific hybrids have been developed by the fish breeders. DNA based markers are ideal elucidation of the fundamental associated with inheritance and linkage in determinate hybrids. First generation markers (Microsatellite, RAPD, ISSR etc.) have limitations when applied to characterize intraspecific hybrids. This study set forth to overcome this limitation by developing the second generation of non-coding non informative anonymous nuclear markers (ncni-ANM) for subsequent genetic characterization of Fl grouper hybrids. Smallinsert genomic DNA library of Epinephelus lanceolatus (EL) and Epinephelus fuscoguttatus (EF) were constructed via a shotgun approach following which they were annotated, subjected to a similarity searches using the blastn algorithms and deposited at the GenBank. Annotated genomic sequences of E lanceolatus and E fuscoguttatuswere than used for designation of anonymous nuclear markers (ANM) and further categorized into being non-coding non-informative ANM (ncni-ANM), non-coding informative ANM (nci-ANM) or coding informative ANM (ci-ANM). Intraspecific DNA fingerprinting analysis was carried out using five E lanceo/atus and 12 E fuscoguttatus broodstock, scored as binary matrix and calculated for genetic distance (GD), genetic similarity (GS) and cophenetic correlation index (CCC) via Jaccard's and Dice's coefficient. An unweighted pair-group method with arithmetic mean (UPGMA) phenogram was constructed based on the GD and CCC values to verify the genetic relationship among the grouper broodstock operational taxonomic units (OTUs). Subsequently, thirty two half-sib Fl hybrids obtained by crossing of female E fuscoguttatus and male E /anceo/atus (EFEL) brooders were characterized using 34 male E. lanceolatus and 32 E. fuscoguttatus ncni-ANM in order to evaluate Mendelian segregation pattern based on genetic inheritance and segregation distortion analyses. A library of 127 genomic sequences was developed of which seven E. lanceolatus and 16 E. fuscoguttatus sequences could be mapped back to the Dicentrarchus labrax genome. Locus specific markers were developed using 60 E. lanceolatus and 67 E. fuscoguttatus genomic sequences. A total of 46 £ lanceolatus ANM were designed containing 34 ncni-ANM, 4 nci-ANM and 8 ci-ANM. While as in total of 42 E. fuscoguttatus ANM were designed containing 32 ncni-ANM, 3 nci-ANM and 7 ci-ANM. Polymerase chain reaction (PCR) amplification patterns of ncni-ANM in both £ lanceolatus and £ fuscoguttatus broodstocks revealed 11 £ lanceolatus and 10 E. fuscoguttatus ncni-ANM were reproducible. Among these 13 E. lanceolatus and E. fuscoguttatus ncni-ANM loci ranged in size from 153 to 177 bp and 157 to 624 bp respectively revealing variation across all OTUs through visualization of agarose gel electrophoresis patterns and binary matrix scoring. Clustering comparison based on CCC goodness-of-fit showed both species samples were best presented using Jaccard's coefficient. The phenogram constructed for the five E /anceolatus OTUs showed two clusters with polyphyletic groups. The first cluster (Cl) consisted of OTUs EL6924, EL5477 and EL140E with monophyletic group while as the second cluster (C2) consisted of OTUs EL4E4D and EL174A with